The U2AF35-related protein Urp contacts the 3′ splice site to promote U12-type intron splicing and the second step of U2-type intron splicing - Shen, Haihong (Cold Spring Harbor Laboratory Press, 2010)
The U2AF35-related protein Urp has been implicated previously in splicing of the major class of U2-type introns. Here we show that Urp is also required for splicing of the minor class of U12-type introns. Urp is recruited in an ATP-dependent fashion to the U12-type intron 3′ splice site, where it promotes formation of spliceosomal complexes. Remarkably, Urp also contacts the 3′ splice site of a U2-type intron, but in this case is specifically required for the second step of splicing. Thus, through recognition of a common splicing element, Urp facilitates distinct steps of U2- and U12-type intron splicing.